0049 Developing perceptions of living with dementia through virtual reality simulation. (2nd November 2015) - Graham, Sean; Bluteau, Patricia; Adefilia, Arinola; Ball, Steven; Clouder, Deanne
Abstract : This presentation outlinses the rationale and development for a virtual reality resource that simulates some of the apparent effects of dementia. Background: Dementia is a progressive condition that affects approximately 800, 000 people in the UK. 1 By 2051, this is expected to rise to 1.7 million 2 placing a heavy burden on health and social care resources. The Francis Report 3 highlights a fundamental need for compassion in care. Dementia is a particularly hard condition for carers to understand as people with dementia can lack the awareness and ability to articulate their needs. Description: The project aimed to enhance understanding of how it might feel to live with dementia so that students studying for a career in health and social care can better empathise with people living with dementia. This was achieved by simulating some apparent effects of the condition, with aged related impairments, through Virtual Reality (VR). Students used the 'think aloud technique' to share and reflect on their experience. Outcomes: Working with a team of specialists, including Professor Graham Stokes (Director of Dementia Care, BUPA), we were able to create a scenario that reflects the current understanding of dementia. We chose to deliver this through VR so user could experience a sense of presence not achievable through typical exercises. In the simulation, the students conducted simple tasks, such as clearing away breakfast dishes. During this engagement the computer logic would mislead the player, and make changes to the environment that weren't in the field of vision. This helped give a sense of confusion. Take home messages: The presentation will discuss the student experience, development journey, costs, and utilising VR as an educational resource. We believe VR is a powerful and accessible new platform, and through our presentation we hope to share our experiences and encourage innovation and exploration. References: https://www.gov.uk/government/uploads/system/uploads/attachment_data/file/142573/Creating_dementia_friendly_hospitals.pdf http://www.alzheimers.org.uk/site/scripts/press_article.php?pressReleaseID=1059 http://webarchive.nationalarchives.gov.uk/20130107105354/http:/www.dh.gov.uk/en/Publicationsandstatistics/Publications/PublicationsPolicyAndGuidance/DH_113018